RESEARCH ON PASSIVE SOIL DEPRESSURIZATION SYSTEMS: STATE OF THE ART AND LAB TEST ON-GOING. Issue 2 (29th October 2020) - Fuente, Marta; Hung, Le Chi; Goggins, Jamie; Foley, Mark
Abstract: There is strong evidence both internationally and in Ireland that the correct installation of passive prevention systems in new buildings is the most cost-effective way of protecting the population against radon. Previous work considering membranes, granular fill material in the aggregate layer beneath the slab and sump system has been conducted in Ireland to improve the protection of buildings from radon. The implications of research on passive sumps potential to reduce radon concentrations are significant, as if it can be shown that the installation of passive sumps in Irish building is effective; this could constitute a low-cost, passive, sustainable method for minimizing radon levels in buildings. On-going experimental tests investigating the performance of different common cowls used for passive soil depressurization systems are presented, in addition to the impact of different vertical heights and horizontal lengths of pipe with a number of bends investigated.